Growth data from a field trial of Quercus suber plants regenerated from selected trees and from their half-sib progenies by somatic embryogenesis (Acta Horticulturae, 2009)
The development of reliable clonal propagation technologies is a requisite for performing Multi-Varietal Forestry (MVF). Somatic embryogenesis is considered the tissue culture based method more suitable for operational breeding of forest trees. Vegetative propagation is very difficult when tissues are taken from mature donors, making clonal propagation of selected trees almost impossible. We have been able to induce somatic embryogenesis in leaves taken from mature oak trees, including cork oak (Quercus suber). This important species of the Mediterranean ecosystem produces cork regularly, conferring to this species a significant economic value. In a previous paper we reported the establishment of a field trial to compare the growth of plants of somatic origin vs zygotic origin, and somatic plants from mature trees vs somatic plants from juvenile seedlings. For that purpose somatic seedlings were regenerated from five selected cork oak trees and from young plants of their half-sib progenies by somatic embryogenesis. They were planted in the field together with acorn-derived plants of the same families. After the first growth period, seedlings of zygotic origin doubled the height of somatic seedlings, showing somatic plants of adult and juvenile origin similar growth. Here we provide data on height and diameter increases after two additional growth periods. In the second one, growth parameters of zygotic seedlings were also significantly higher than those of somatic ones, but there were not significant differences in height increase between seedlings and somatic plants of mature origin. In the third growth period, height and diameter increases of somatic seedlings cloned from the selected trees did not differ from those of zygotic seedlings, which were still higher than data from plants obtained from somatic embryos from the sexual progeny. Therefore, somatic seedlings from mature origin seem not to be influenced by a possible ageing effect, and plants from somatic embryos tend to minimize the initial advantage of plants from acorns.

Growth data from a field trial of Quercus suber plants regenerated from selected trees and from their half-sib progenies by somatic embryogenesis - Celestino, Cristina; Fernandez-Guijarro, B.; Hernández, Inmaculada; López Vela, Dolores; Carneros, Elena; Jiménez García, Jesús; Cardo, L.; Alegre, Jesús; Toribio, Mariano (Acta Horticulturae, 2009)
The development of reliable clonal propagation technologies is a requisite for performing Multi-Varietal Forestry (MVF). Somatic embryogenesis is considered the tissue culture based method more suitable for operational breeding of forest trees. Vegetative propagation is very difficult when tissues are taken from mature donors, making clonal propagation of selected trees almost impossible. We have been able to induce somatic embryogenesis in leaves taken from mature oak trees, including cork oak (Quercus suber). This important species of the Mediterranean ecosystem produces cork regularly, conferring to this species a significant economic value. In a previous paper we reported the establishment of a field trial to compare the growth of plants of somatic origin vs zygotic origin, and somatic plants from mature trees vs somatic plants from juvenile seedlings. For that purpose somatic seedlings were regenerated from five selected cork oak trees and from young plants of their half-sib progenies by somatic embryogenesis. They were planted in the field together with acorn-derived plants of the same families. After the first growth period, seedlings of zygotic origin doubled the height of somatic seedlings, showing somatic plants of adult and juvenile origin similar growth. Here we provide data on height and diameter increases after two additional growth periods. In the second one, growth parameters of zygotic seedlings were also significantly higher than those of somatic ones, but there were not significant differences in height increase between seedlings and somatic plants of mature origin. In the third growth period, height and diameter increases of somatic seedlings cloned from the selected trees did not differ from those of zygotic seedlings, which were still higher than data from plants obtained from somatic embryos from the sexual progeny. Therefore, somatic seedlings from mature origin seem not to be influenced by a possible ageing effect, and plants from somatic embryos tend to minimize the initial advantage of plants from acorns.
Keywords: Cork oak; field establishment; forest improvement; rejuvenation; vegetative propagation; woody plant micropropagation